REAL-TIME JAUNDICE DETECTION IN NEWBORNS USING SKIN COLOR SCANNING METHOD - Fratidhina, Yudhia; Mulyati, Sri; Astri, Hetty; Aminoto, Toto (Universitas Aisyah Pringsewu, 2025)
Neonatal jaundice is a common condition that can lead to severe complications if not detected and treated early. This study focuses on the development of a non-invasive jaundice detection tool using a TCS3200 color sensor, which aims to provide early diagnosis by measuring skin discoloration associated with elevated bilirubin levels. The methodology for the study involved several stages: designing the device, calibrating the color sensor, and conducting field tests in clinical settings. The TCS3200 sensor was used to capture the skin color from various body areas of newborns, including the forehead, chest, abdomen, and limbs. The collected data were correlated with serum bilirubin levels, and the severity of jaundice was classified using the Kramer scale, a clinical tool that assesses the spread of yellow pigmentation across the body. The results showed that the jaundice detection tool achieved a high degree of accuracy, with its readings closely mirroring laboratory-based bilirubin measurements. This was particularly evident in cases of moderate to severe jaundice, where the tool provided precise early detection. The non-invasive nature of the tool, combined with its portability, makes it an ideal solution for use in healthcare facilities with limited access to laboratory equipment. Additionally, the tool can be operated by healthcare workers with minimal training, which enhances its potential for deployment in rural or underserved areas. The study concludes that the developed jaundice detection tool has significant potential to improve neonatal care by enabling early diagnosis and timely intervention, thereby reducing the risk of severe jaundice-related complications. Future research will focus on scaling up the testing of the device across a larger and more diverse population of newborns, as well as pursuing product certification to facilitate broader implementation in healthcare settings.